Policy Implementation of PSU Handover in Griya Srimahi Indah Housing - Lia Fanny; Yulianto Yulianto (Journal of Public Representative and Society Provision, 2026)
This study examines the implementation of the policy for handing over infrastructure, facilities, and utilities in supporting settlement suitability in Griya Srimahi Indah Housing, Bekasi Regency. The policy is intended to ensure that basic settlement facilities are managed by the local government after being handed over by private developers. The study addresses three main questions: how the handover policy is implemented, what major challenges arise in the process, and what roles are played by key stakeholders. A qualitative case study approach is employed, using in‑depth interviews, non‑participant observation, and document analysis. The findings show that implementation is partial and has not fully achieved the intended objectives. In terms of communication, coordination between government agencies remains inconsistent. Regarding resources, there are limitations in technical human resources within the local government and limited budget support. In terms of disposition, implementers show uneven commitment in completing administrative procedures. From the bureaucratic structure perspective, handover procedures are fragmented across several work units. Stakeholders such as the local government, the developer, and residents have differing interests, while coordination mechanisms have not been optimally developed. The study concludes that policy implementation proceeds at an inconsistent pace, constrained by a structural context that does not sufficiently support consistent implementation and by stakeholder roles that are not yet facilitated through structured policy communication and participation.